Frontispiece: An Overview of Structural Features of Antibacterial Glycoconjugate Vaccines That Influence Their Immunogenicity. Issue 18 (28th March 2017) - Khatun, Farjana; Stephenson, Rachel J.; Toth, Istvan
Abstract : Glycoconjugate Vaccines Immunogenic carbohydrate chains derived from the bacterial capsular polysaccharides, lipoteichoic acid and lipopolysaccharides are used as B cell antigens to develop glycoconjugate vaccines. To boost the immune activity of these antigens, immunogenic carrier proteins (T cell antigens) are covalently conjugated with/without the help of spacer molecule(s) by using appropriate conjugation chemistry. Structurally defined neoglycoconjuagtes consist of short‐chain carbohydrates attached to single carrier protein, whereas structurally complex cross‐linked glycoconjugates composed of multiple active sites containing long‐chain carbohydrates conjugated to single/multiple protein(s). Both of these vaccines are effective against bacterial infectious diseases. For more details, see the Review article by I. Toth et al. onpage 4233 ff.